Phát triển các module rèn luyện nghiệp vụ sư phạm thường xuyên tích hợp hoạt động sử dụng tiếng Anh chuyên ngành cho sinh viên ngành Giáo dục mầm non, Trường Đại học Thủ đô Hà Nội - Ha, T C Nhung; Đặng Lan Phương, Đặng Lan Phương (Tạp chí Giáo dục, 2026)
Under the framework of Circular No. 50/2020/TT-BGDĐT and Professional Standards for Preschool Teachers, there is an urgent mandate to equip future preschool teachers with bilingual proficiency to meet the demands of international integration. However, current training at Hanoi Metropolitan University (HNMU) reveals a significant disconnection between academic linguistic theory and professional practice. Consequently, while students may meet general language standards, they often lack the specific skills required to apply English in authentic occupational environments. This study employs a parallel mixed-methods research design. Quantitative data were gathered from 191 Early Childhood Education (ECE) students through Likert-scale questionnaires, while qualitative insights were obtained from semi-structured interviews with 10 specialized lecturers. Furthermore, a curriculum matrix analysis was conducted to cross-examine the Learning Outcomes (PLO/CLO) of the six existing Regular Pedagogical Training (RPT) modules. Findings highlight a severe misalignment between academic proficiency and professional application. Notably, 81.9% of students encounter major obstacles when using English for child assessment, with a mean score of only 1.92/5 in this specific pedagogical task. In contrast, student demand for technological integration is exceptionally high, with over 88% expressing a desire to utilize AI Chatbots to enhance their communicative reflexes. Based on these empirical needs, the study proposes a framework for integrating English for Specific Purposes (ESP) activities into the six-semester RPT roadmap, progressing from A2 to B1 levels. This model features a specialized content matrix and a three-step pedagogical process supported by digital learning resources. The study concludes that such integration is essential for transforming English from a mere “prerequisite subject” into a functional “professional tool”. It is recommended that teacher-training institutions prioritize the standardization of integrated assessment rubrics and the upgrade of Learning Management System (LMS) infrastructure. These solutions serve as a critical foundation for fostering bilingual professional identities among ECE students in the era of global educational integration.